(3TQM GdYhGed GdeFIs - (3jMji Hf fUhM Hf ESQGFjd, GdeYQha H` jMji LdHjs; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3hHYO, ajbhd jMji GHf fUhM Hf ESQGFjd GYdehG jGeYGTQ WdGH Gdjbjf s
(3BNQgG (B:s
(3adG jSJZfj GdUZjQ hGdcHjQ EP HgG jMUd dge HUjQI aj GdYdhe cdgG ef aVd Gddg JYGdi Cf jLYd eG LeYJg NGdUkG dMVQJg GdehUha HGdcQe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Cdag ddSdWGf eUWai Hf SdjeGf NGf GdYKeGfjs
(3HChdgG JedcGJ CbOegG SfI (B1197(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs